INVESTMENT DECISION OF DKI JAKARTA MILLENNIALS IN ISLAMIC PEER-TO-PEER FINANCING DURING THE COVID-19 PANDEMIC - Destiana Rahmawati Dewi; Laily Dwi Arsyianti (Universitas Airlangga, 2023)
DKI Jakarta is the region with the highest proportion of internet users from the total population of each province on the island of Java, including in terms of the use of Financial Technology (FinTech). Islamic Peer-To-Peer Financing (IP2PF) is one type of FinTech that is an investment choice for millennials, but Islamic FinTech users from the investor side are still very few, especially during the COVID-19 pandemic. This research aims to find out the factors that influence the investment decisions of DKI Jakarta millennials in IP2PF during the COVID-19 pandemic through a sample of 100 DKI Jakarta millennial investors. The methods used are descriptive analysis and binary logistic regression with IBM SPSS Statistics 22 software tools. The results showed that during the COVID-19 pandemic, Islamic financial literacy, IP2PF knowledge, trust, social environment, gender, and income had a significant positive effect on investment decisions in IP2PF. Therefore, the IP2PF should closely build engagement to their customers, enlarge literacy coverage in supported by government to build the ecosystem.